Breast Cancer in the Modern Era: A Comprehensive Review on Advances in Understanding and Managing Breast Cancer - Khizar , Wafa; Hussain , Shahzad; Riaz , Humayun; Kaleem , Laraib; Zaheer, Hajra; Latif , Ranaz; Ghaffar , Abdul; Godman , Brian; Ali, Ahmed (Indus Journal of Bioscience Research, 2025)
Even with advances in screening and prevention methods, breast cancer is more often diagnosed in women than any other malignancy. An increased knowledge of genetics made it possible for researchers to sort breast cancer into four types: luminal A, luminal B, HER2‑enriched, and triple‑negative, all marked by specific biomarkers and estimations for the outcome. High‑throughput genomic classifiers such as the Breast Cancer Classifier (BCC) have allowed doctors to more accurately choose the best medicine for HER2‑low tumors. Now, liquid biopsies and multiplex immunofluorescence tests are being used, in addition to imaging and samples taken from tissue, to help recognize minimal amounts of disease at an early stage. Among hormone receptor‑positive and BRCA‑mutant patients, CDK4/6 inhibitors, antibody–drug conjugates, and PARP inhibitors have improved progression‑free survival. Tools powered by artificial intelligence are regularly being included in the work of many health professionals, helping them detect diseases more accurately and measure a patient’s probability of illness. However, because some cancer treatments can cause serious side effects in young people and early menopause, efforts are being made to trial new therapies that focus clearly on how these patients feel after surviving cancer. There is a need to explore how neoadjuvant therapy can be improved, use different kinds of data for assessing treatment needs, and ensure that all patients receive the best treatment available. The current review aimed to investigate advances in understanding and managing breast cancer.